Evolutionary Quantitative Genetics - Roff, Derek A. (Springer US : Imprint : Springer, 1997)
This new textbook in quantitative genetics incorporates an evolutionary viewpoint, combining the theoretical basis of quantitative genetics with respect to evolution in natural populations and various statistical methods of analysis. Topics of current research such as genetic correlation and phenotypic plasticity are included. The book addresses the current problems in quantitative genetic evolutionary theory and presents the most commonly used methods of analysis.